One-node and two-node hybrid coarse-mesh finite difference algorithm for efficient pin-by-pin core calculation - Song, Seongho; Yu, Hwanyeal; Kim, Yonghee (Nuclear engineering and technology, 2018)
This article presents a new global–local hybrid coarse-mesh finite difference (HCMFD) method for efficient parallel calculation of pin-by-pin heterogeneous core analysis. In the HCMFD method, the one-node coarse-mesh finite difference (CMFD) scheme is combined with a nodal expansion method (NEM)–based two-node CMFD method in a nonlinear way. In the global-local HCMFD algorithm, the global problem is a coarse-mesh eigenvalue problem, whereas the local problems are fixed source problems with boundary conditions of incoming partial current, and they can be solved in parallel. The global problem is formulated by one-node CMFD, in which two correction factors on an interface are introduced to preserve both the surface-average flux and the net current. Meanwhile, for accurate and efficient pin-wise core analysis, the local problem is solved by the conventional NEM-based two-node CMFD method. We investigated the numerical characteristics of the HCMFD method for a few benchmark problems and compared them with the conventional two-node NEM-based CMFD algorithm. In this study, the HCMFD algorithm was also parallelized with the OpenMP parallel interface, and its numerical performances were evaluated for several benchmarks. Keywords: Hybrid Coarse-Mesh Finite Difference Method, One-Node Coarse-Mesh Finite Difference, Parallel Computation, Pin-By-Pin Analysis, Two-Node Coarse-Mesh Finite Difference